2021
DOI: 10.1016/j.cortex.2020.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal dynamics of signal selective motor plan cancellation in the macaque dorsal premotor cortex

Abstract: Primates adopt various strategies to interact with the environment. Yet, no study has examined the effects of behavioral strategies with regard to how movement inhibition is implemented at the neuronal level. We modified a classical approach to study movement control (stop-task) by adding an extra signal-termed the Ignore signal-which influenced movement inhibition only under a specific strategy. We simultaneously recorded multisite neuronal activity from the dorsal premotor (PMd) cortex of macaque monkeys dur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 57 publications
5
22
0
Order By: Relevance
“…To tackle this issue, we recorded single neuronal activity from PMd of rhesus monkeys while performing the countermanding task (8)(9)(10)(11)(12). In this task, a Stop signal presented in some trials during the reaction time asks for the cancellation of a movement during the motor plan development.…”
Section: Introductionmentioning
confidence: 99%
“…To tackle this issue, we recorded single neuronal activity from PMd of rhesus monkeys while performing the countermanding task (8)(9)(10)(11)(12). In this task, a Stop signal presented in some trials during the reaction time asks for the cancellation of a movement during the motor plan development.…”
Section: Introductionmentioning
confidence: 99%
“…The effector-dependent stopping mechanisms are slower but may provide flexibility during time-insensitive behaviors. Such flexibility in brain and behavioral mechanisms have also been observed in selectively stopping actions [ 30 , 90 ] (see [ 91 ]).…”
Section: Significancementioning
confidence: 99%
“…Prior research has shown that stopping eye and hand movements are thought to be mediated by anatomically separate regions. Eye movements are thought to be stopped by distinct populations of neurons in the frontal eye field and superior colliculus [ 26 , 27 , 28 ], while cortical regions, such as the right inferior frontal cortex, pre-supplementary motor area, premotor and primary motor cortex, are important for stopping manual movements [ 29 , 30 , 31 , 32 ]. However, Leung and Cai (2007) [ 33 ] have reported both overlapping and non-overlapping activations in the prefrontal cortex during the stopping of saccades and button presses, suggesting that both common or separate nodes might mediate the stopping of coordinated eye–hand movements.…”
Section: Introductionmentioning
confidence: 99%
“…Here, aiming to contribute to the understanding of the role of the dorsal premotor (PMd) cortex in arm motor control [8][9][10] we studied the local spiking activity (SA) derived from a multi-electrode array and implemented a combined information-theory and topological approach to describe how the collective activity of mesoscopically-defined local modules is linked to motor decision-making. Indeed, it has been shown that neurons express more their contribution to complex behavioural functions either when observed as coordinated functional ensembles [11][12][13][14][15][16][17][18][19] or described as common responses to the input they receive (e.g., the visual stimulus orientation columns 20 ). A paradigmatic example is the interaction between fixation and movement neurons in the epochs preceding saccade generation 13,14 .…”
Section: Introductionmentioning
confidence: 99%